Long‐term follow up of paediatric liver transplant recipients: outcomes following transfer to adult healthcare in New Zealand. Issue 5 (May 2015) - Harry, R.; Fraser‐Irwin, C.; Mouat, S.; Gane, E.; Munn, S.; Evans, H. M.
Abstract Poor outcomes are reported in young people with chronic health conditions. We performed a retrospective notes review of New Zealand paediatric liver transplant recipients transferred to adult services. Two patients were lost to follow up. Out of 20, 12 were non‐adherent, and out of 12, 7 developed rejection. Other risk behaviours were common in the non‐adherent group. We conclude that dedicated services for these young people may be needed to optimise outcomes.